Criterion validity of two mobile applications to count the number of steps in older adults with chronic pain. (3rd September 2021) - Ferreira, José; Queirós, Alexandra; Silva, Anabela G.
Abstract: Aim: Mobile applications to count the number of steps can be used to promote physical activity. However, its accuracy is seldom tested in older adults with pain. This study aimed to assess the criterion validity of two mobile applications to measure the number of steps in older adults with pain, and whether it was affected by gait velocity, type of path and smartphone position. Methods: Fifty old adults with chronic pain were asked to walk on different paths and at different velocities with two mobile applications (Pedometro – Step Counter and EasyFit Pedometer), running on a smartphone positioned at the arm and the front pocket of the trousers. Mobile applications counting were compared against the manual counting of an observer. Results: Correlations between manual counting and app measurements were ≥0.99 for Pedometro and between – 0.35 and 0.24 for EasyFit Pedometer; mean percentage differences were below 10% for the first app and above 10% for 9 out of 10 comparisons for the second. Conclusion: Only the Pedometer – Step Counter was able to accurately count the number of steps independently of path and smartphone position. These suggest the need to assess the validity of mobile apps before making them available to the public.